Diagnosis and management of urethro-cavernosal fistulas. (November 2020) - Han, Jullet; Ghodoussipour, Saum; Kreydin, Evgeniy I; Doumanian, Leo
Objective: To present a case series of urethro-cavernosal fistulas evaluating their diagnostic work-up and management. Methods: A literature search was performed using key words including "urethro-cavernosal fistula, " "urethral fistula, " and "cavernosal fistula." Results: In total 10 case reports were identified and reviewed for information regarding clinical diagnosis, management, and long-term outcomes including success rates and complications. Conclusion: Urethro-cavernosal fistula is a rare urological condition. With few cases reported to date, there is considerable variation in diagnostic work-up and management. Both conservative and surgical approaches can be utilized in the management of urethro-cavernosal fistulas with good long-term outcomes. Level of evidence: Not applicable for this multicentre audit.